Characterization and Combustion Kinetics of Chars Obtained from Loquat Stones - Sutcu, Hale; Piskin, Sabriye (TAYLOR & FRANCIS INC, 2009)
This paper describes the production of chars from loquat stones in a tube furnace at carbonization temperatures of 600C, 700C, and 800C in a nitrogen flow at a heating rate of 10C/min. The physical and chemical structures of the stones and chars were investigated by FTIR spectrometer, X-ray diffractometer, and SEM, as well as the combustion reaction and kinetic parameters based on the TG-DTG graphs obtained by thermogravimetric analysis. The combustion reaction was carried out at a heating rate 10C/min and an oxygen flow rate of 50ml/min up to 700C. The kinetic parameters were calculated using the methods by Arrhenius; Coats and Redfern; Horowitz and Metzger; and Ingraham and Marier.
Keywords: Arrhenius; Char; Coats and Redfern; Combustion; Horowitz and Metzger; Ingraham and Marier; Loquat stone; Thermogravimetric analysis; CHINESE BITUMINOUS COAL; PYROLYSIS; WOOD; CHARCOALS; BIOMASS; Thermodynamics; Energy & Fuels; Engineering